On The Scalability of Dye-Sensitized Solar Cells : Effect of Photoelectrode Area on the Photovoltaic and Charge Transport Parameters - Rajan, Jose; Fakharuddin, Azhar; Panikar, Sathyaseelan Archana; M. M., Yusoff (2013)
This study is aimed to provide new insights on the scalability of dye-sensitized solar cells (DSCs). The DSCs of electrode area up to ~2 cm2 were fabricated using commercially available P25 TiO2 particles, N3 dye, and iodide/triiodide electrolyte and evaluated using voltage - current and electrochemical impedance spectroscopic measurements. The photovoltaic conversion efficiency follows a biexponential decay, the main contributor to which is the short circuit current density(JSC). Interesting features were observed in the electrochemical impedance spectra and charge transport parameters in the devices as the photoelectrode areas are increased. Results show that electrons from an area above a threshold are not collected due to varied choice of diffusion pathways. Furthermore, this study identify that area of the photoelectrode for reporting the efficiency needs to be fixed at ~0.5 cm2 for 25 nm TiO2 particles because below which it strongly vary. On the other hand, the study provides opportunities to build high efficiency dye-sensitized solar cells using the current choice of materials.